A hybrid adsorption material for adsorbing trace organic pollutants in water and its preparation and application
By preparing MOF/cellulose hybrid adsorption materials, the problem of lack of selectivity of adsorbent materials in the prior art is solved, and efficient adsorption and selective removal of trace organic pollutants in water is achieved, with good regeneration and environmental friendliness.
Patent Information
- Application Number
- CN202310072264.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-02-02
AI Technical Summary
Existing adsorbent materials lack selectivity in treating trace organic pollutants in water, resulting in inefficiency and environmental pollution.
Using MOF/cellulose hybrid adsorption material, natural cellulose is oxidatively modified by delignin and TEMPO, combined with in-situ synthesis of metal organic framework materials, to form an adsorption material with high porosity and selective adsorption ability.
It realizes efficient adsorption of trace organic pollutants in water, especially selective adsorption effect on cationic dyes, and the material can be reused, with good regeneration and environmental friendliness.
Smart Images

Figure CN116059982B_ABST
Abstract
Description
Technical Field
[0001] The invention specifically relates to a hybrid adsorption material for adsorbing trace organic pollutants in water and preparation and application thereof, belonging to the field of adsorption materials. Background Art
[0002] There are various trace organic pollutants in slightly polluted water sources, which not only have a wide range of pollution, a large total amount, complex composition, but also are very toxic. Organic matter in water can be roughly divided into natural organic matter and artificially synthesized organic matter. There are many types of artificially synthesized organic matter, including chlorobenzenes, pesticides, phenols, polychlorinated biphenyls and polybrominated diphenyl ethers, nitrobenzenes and phthalates. Although these organic matter have low concentrations, they are of various types and have high mutagenic activity, which is extremely harmful to human health. Organic matter remains in water for a long time and is not easy to degrade, which will have a serious impact on the air environment, soil environment and water environment.
[0003] Dye wastewater has the characteristics of complex composition, high chemical oxygen demand, deep chroma, high toxicity, and difficulty in degradation. It will cause serious pollution to the environment and threaten the water environment safety of the basin. Crystal violet (CV) dye is a typical triphenylmethane dye. Toluene and other substances in it will reduce the permeability of water bodies and affect the photosynthesis and normal growth of aquatic organisms. In addition, if it flows into the human body through the circulation chain, it will cause some serious harm to the human body, such as carcinogenicity, teratogenicity, and mutagenicity.
[0004] At present, among the reported treatment methods for organic pollutants, adsorption is considered to be a promising treatment method due to its high cost-effectiveness, good reuse, simple operation, high adsorption efficiency, and low possibility of secondary pollution. Commonly used adsorbent materials for wastewater treatment include activated carbon, bentonite, diatomaceous earth, zeolite, etc., but these common adsorbents do not have adsorption selectivity. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the present invention provides a hybrid adsorption material capable of adsorbing trace organic pollutants in water, and a preparation method and application thereof.
[0006] The technical solution adopted by the present invention to solve the technical problem is:
[0007] The present invention provides a method for preparing a MOF / cellulose hybrid adsorption material for adsorbing trace organic pollutants in water, comprising the following steps:
[0008] (1) dissolving sodium chlorite in water and adjusting the pH to 2-6 using an acetic acid buffer to obtain a mixed solution; then adding wood to the mixed solution and subjecting it to hydrothermal treatment to obtain delignified wood;
[0009] (2) immersing the delignified wood obtained in an aqueous solution containing TEMPO and NaBr, then adding sodium hypochlorite and adjusting the pH to 8-12 for oxidation reaction; after the reaction is completed, taking out the wood, washing it, and drying it to obtain oxidatively modified wood;
[0010] (3) Dissolving zirconium salt and terephthalic acid in N,N-dimethylformamide solvent respectively, and mixing to obtain two solutions; then mixing the two solutions, adding the oxidized modified wood obtained in step (2), and reacting at 100-150° C.; after the reaction, adjusting the pH to neutral, taking out the wood, washing, and drying to obtain a MOF / cellulose hybrid adsorption material.
[0011] In one embodiment of the present invention, in step (1), the concentration of sodium chlorite dissolved in water is (1-10) g / (10-100) mL.
[0012] In one embodiment of the present invention, in step (1), the amount of the mixed liquid relative to the wood is (10-100) mL / g.
[0013] In one embodiment of the present invention, in step (1), the hydrothermal treatment is carried out at a constant temperature of 40-100° C. with continuous stirring for 2-20 hours.
[0014] In one embodiment of the present invention, in step (2), the amount of the aqueous solution containing TEMPO and NaBr relative to the delignified wood is (10-100) mL / g.
[0015] In one embodiment of the present invention, in step (2), the mass ratio of TEMPO to NaBr in the aqueous solution containing TEMPO and NaBr is (0.001-0.1):(0.1-1).
[0016] In one embodiment of the present invention, in step (2), the concentration of NaBr in the aqueous solution containing TEMPO and NaBr is (0.1-1) g / (10-100) mL.
[0017] In one embodiment of the present invention, in step (2), the amount of sodium hypochlorite used relative to the delignified wood is 10-50 mL.
[0018] In one embodiment of the present invention, in step (2), the oxidation reaction is carried out at a constant temperature of 20-50° C. for 5-10 hours.
[0019] In one embodiment of the present invention, in step (3), the zirconium salt may specifically be zirconium chloride.
[0020] In one embodiment of the present invention, in step (3), the mass ratio of zirconium chloride to terephthalic acid is (0.01-0.5):(0.01-0.3).
[0021] In one embodiment of the present invention, in step (3), 0.01-0.5 g of zirconium chloride and 0.01-0.3 g of terephthalic acid are respectively dissolved in 10-50 mL of N,N-dimethylformamide solvent to prepare a corresponding solution.
[0022] In one embodiment of the present invention, in step (3), the reaction time is 10-30 hours.
[0023] In one embodiment of the present invention, in step (3), the reaction temperature is preferably 120°C.
[0024] In one embodiment of the present invention, the preparation method specifically includes the following process:
[0025] (1) Preparation of porous cellulose carrier: Take a 150 ml round-bottom flask, dissolve 1-10 g of sodium chlorite in 10-100 ml of deionized water, then add acetic acid buffer to adjust the pH to 2-6, ultrasonicate for 10-30 min, weigh 1 g of dry balsa wood sample and add it; keep stirring at a constant temperature of 40-100 ° C for 2-20 hours to remove lignin; finally, rinse the sample carefully with deionized water to remove chemical residues and store it in deionized water;
[0026] (2) Oxidative modification of cellulose carrier: Delignified wood sample (1 g) was immersed in 10-100 ml of aqueous solution containing 0.001-0.1 g TEMPO and 0.1-1 g NaBr. Then, 10-50 ml of sodium hypochlorite solution was added dropwise to the solution to initiate the oxidation reaction; the pH value of the solution was maintained at 8-12 by adding 0.1 M NaOH, and the reaction was carried out at 20-50° C. for 5-10 hours; then, the pH of the solution was adjusted to neutral by adding 0.5 M HCl to terminate the reaction; the oxidized wood sample was washed with deionized water and stored after freeze-drying;
[0027] (3) Preparation of MOF / cellulose hybrid material: Weigh 0.01-0.5 g of zirconium chloride and 0.01-0.3 g of terephthalic acid, respectively, dissolve them in 10-50 mL of N,N-dimethylformamide solvent, and disperse them evenly by ultrasonication; mix the two solutions and stir for 10-30 min, then put them into a stainless steel high-pressure reactor, and add 1 g of dry wood sample that has been delignified and TEMPO oxidized and modified, and react at 100-150 ° C for 10-30 hours; after cooling, take out the wood sample, and centrifuge and wash the wood sample with an organic solvent for 3-5 times, and freeze-dry to obtain the MOF / cellulose hybrid adsorption material.
[0028] In one embodiment of the present invention, the wood in step (1) is naturally grown balsa wood.
[0029] In one embodiment of the present invention, the freeze-drying time in step (2) and step (3) is 24 hours.
[0030] In one embodiment of the present invention, the stainless steel autoclave in step (3) is a polytetrafluoroethylene lined autoclave.
[0031] In one embodiment of the present invention, the organic solvent in step (3) is DMF or methanol.
[0032] The present invention provides a MOF / cellulose hybrid adsorption material for adsorbing trace organic pollutants in water based on the above preparation method.
[0033] The present invention also provides the use of the MOF / cellulose hybrid adsorption material for adsorbing trace organic pollutants in water in wastewater treatment.
[0034] The present invention also provides the use of the MOF / cellulose hybrid adsorption material for adsorbing trace organic pollutants in water in adsorbing organic pollutants.
[0035] In one embodiment of the present invention, the organic pollutants include: Congo red, crystal violet, methylene blue, methyl orange, rose bengal B, eosin B, bisphenol A, alkylphenols, and tetrabromobisphenol A.
[0036] The present invention also provides the use of the MOF / cellulose hybrid adsorption material for adsorbing trace organic pollutants in water in the selective adsorption of crystal violet.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present invention provides a method for preparing and applying a hybrid adsorbent material capable of adsorbing trace organic pollutants in water, which utilizes the advantages of the porous structure and large specific surface area of the metal organic framework material to provide more adsorption sites for the adsorption of dyes.
[0039] (2) The present invention performs delignification treatment on naturally grown balsa wood. The obtained delignified wood not only retains the cellulose-based cavity of natural wood, but also makes the nanofibers of cellulose microfibers oriented substantially in the same direction, which is beneficial to increase its own porosity.
[0040] (3) The present invention performs TEMPO oxidation modification on delignified wood to oxidize the hydroxyl groups on the cellulose skeleton of delignified wood into carboxyl groups. The resulting wood sample has more microscopic voids, which not only improves its own porosity and specific surface area, but also facilitates subsequent functional modification.
[0041] (4) The present invention synthesizes a hybrid adsorption material by in-situ generation of zirconium-based metal organic framework materials on cellulose, thereby solving the problem that metal organic framework materials are easy to pulverize as adsorbents and are not conducive to efficient recycling. The obtained adsorption material has the characteristics of high porosity, high specific surface area and a large number of adsorption sites, has a good adsorption effect on cationic dyes, and has the characteristics of selective adsorption of crystal violet. The method is simple to prepare and easy to operate, has good repeatability, and stable adsorption performance.
[0042] (5) The adsorption material of the present invention can be reused through desorption, has no destructive effect on the structure of organic matter, has stable adsorption performance, and has good regeneration and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a scanning electron microscope image of the MOF / cellulose hybrid adsorption material in Example 1.
[0044] Figure 2 This is a field emission scanning electron micrograph of the MOF / cellulose hybrid adsorption material in Example 1.
[0045] Figure 3 This is the infrared spectrum of the MOF / cellulose hybrid adsorption material in Example 1. DETAILED DESCRIPTION
[0046] Example 1
[0047] Preparation of MOF / cellulose hybrid adsorption materials:
[0048] (1) Preparation of porous cellulose carrier: Take a 150 ml round-bottom flask, dissolve 1 g of sodium chlorite in 100 ml of deionized water, add acetic acid buffer to adjust pH = 4.6, ultrasonicate for 10 min, and add 1 g of dried balsa wood sample. Stir at constant temperature at 80 ° C for 18 hours to remove lignin. Finally, rinse the sample with deionized water to remove chemical residues, obtain a delignified wood sample, and store it in deionized water.
[0049] (2) Oxidative modification of cellulose carrier: The delignified wood sample (1 g) obtained in step (1) was immersed in 100 ml of an aqueous solution containing 0.1 g of TEMPO and 0.75 g of NaBr. Then, 10 ml of a sodium hypochlorite solution (active chlorine concentration: ≥5.2%) was added dropwise to the solution to initiate an oxidation reaction. The pH value of the solution was maintained at 10.0 by adding 0.1 M NaOH, and the reaction was carried out at a constant temperature of 25° C. for 8 hours. After 8 hours, the pH of the solution was adjusted to neutral by adding 0.5 M HCl to terminate the reaction. The sample was washed with deionized water to obtain an oxidatively modified wood sample, which was freeze-dried and stored.
[0050] (3) Preparation of MOF / cellulose hybrid material: 0.223 g zirconium chloride and 0.166 g terephthalic acid were dissolved in 30 mL DMF respectively, and ultrasonically dispersed uniformly. The two solutions were mixed and ultrasonically dispersed for 10 min, and then placed in a stainless steel autoclave, and 1 g of the oxidatively modified wood sample obtained in step (2) was added, and the reaction was carried out at 120° C. for 24 hours. After cooling, the wood sample was taken out and washed three times with DMF, and then freeze-dried to obtain the MOF / cellulose hybrid adsorption material.
[0051] The MOF / cellulose hybrid adsorption material was tested for adsorption of six dyes: Congo red, crystal violet, methylene blue, methyl orange, rose bengal B, and eosin B:
[0052] Weigh 10 mg of MOF / cellulose hybrid adsorption material, take 60 mL of different dye solutions with an initial concentration of 0.1 mmol / L, add the adsorption material to each dye solution without adjusting the pH, and place it in a constant temperature oscillating water bath at 25°C. After oscillating and adsorbing for 24 hours, the adsorption results of MOF / cellulose hybrid adsorption material on different dyes are tested by ultraviolet absorption spectroscopy.
[0053] According to the test results, the MOF / cellulose hybrid adsorption material basically does not adsorb the three anionic dyes, Rose Bengal B, Congo Red and Eosin B, but has an obvious adsorption effect on cationic dyes. The adsorption amount of methyl orange is 0.09228mmol / g, the adsorption amount of methylene blue is 0.0996mmol / g, and the adsorption amount of crystal violet is 0.1485mmol / g. It can be seen that it has a selective adsorption effect on crystal violet.
[0054] Taking crystal violet dye as the target dye to be adsorbed, the optimal conditions for adsorption were explored:
[0055] 1. Investigate the effect of dye solution pH on adsorption performance. Weigh multiple portions of 10 mg MOF / cellulose hybrid adsorption material, take multiple portions of 60 mL of dye solution with an initial concentration of 0.1 mmol / L, adjust the pH of the dye solution to 2 to 12, add the adsorbent material to the dye solution, and place it in a constant temperature oscillating water bath at 25°C. After 24 hours of oscillation adsorption, compare the adsorption amounts through ultraviolet absorption spectroscopy test to obtain the optimal pH.
[0056] 2. Investigate the effect of adsorption time. Weigh multiple portions of 10 mg MOF / cellulose hybrid adsorption material, take multiple portions of 60 mL of dye solution with an initial concentration of 0.1 mmol / L, adjust the pH of the dye solution to the best, add the adsorbent material to the dye solution, and place it in a constant temperature oscillating water bath at 25°C, oscillate and adsorb for different times (1-24h), compare the adsorption amount through ultraviolet absorption spectrum test, and obtain the best adsorption time.
[0057] 3. Investigate the effect of initial dye concentration on adsorption. Weigh multiple portions of 10 mg MOF / cellulose hybrid adsorption material, take 60 mL of dye solution with different initial concentrations, adjust the solution pH to the best, add the adsorption material to the solution, and place it in a constant temperature oscillating water bath at 25°C. The oscillation adsorption time is the best time. Through ultraviolet absorption spectrum test, compare the adsorption amounts and obtain the best initial concentration.
[0058] When the adsorption temperature was 25℃, the optimal adsorption conditions were: the initial concentration of the dye solution was 8mM, the pH was 8, and the adsorption time was 1080min. Under these conditions, the maximum adsorption amount of crystal violet was 19.99mmol / g.
[0059] Adsorption selectivity test for crystal violet: weigh 10 mg of MOF / cellulose hybrid adsorption material, take 60 mL of mixed dye solution (including crystal violet, cresol red, thymol blue, naphthol green, and Congo red, each with a concentration of 8 mM), add the adsorbent material to the mixed dye solution without adjusting the pH, and place it in a constant temperature oscillating water bath at 25 ° C. After oscillating and adsorbing for 24 hours, the concentration of various dyes in the mixed dye solution is tested. The results show that the adsorption capacity of the adsorbent for crystal violet is 17.21 mmol / g, while there is no adsorption of other dyes, which indicates that the adsorbent of this embodiment has adsorption selectivity for crystal violet.
[0060] Example 2
[0061] (1) Preparation of porous cellulose carrier: Take a 150 ml round-bottom flask, dissolve 1 g of sodium chlorite in 100 ml of deionized water, add acetic acid buffer to adjust pH = 4.6, ultrasonicate for 10 min, and add 1 g of dried balsa wood sample. Stir at constant temperature at 80 ° C for 18 hours to remove lignin. Finally, rinse the sample with deionized water to remove chemical residues, obtain a delignified wood sample, and store it in deionized water.
[0062] (2) Oxidative modification of cellulose carrier: The delignified wood sample (1 g) obtained in step (1) was immersed in 100 ml of an aqueous solution containing 0.1 g of TEMPO and 0.75 g of NaBr. Then, 10 ml of sodium hypochlorite solution was added dropwise to the solution to initiate an oxidation reaction. The pH value of the solution was maintained at 10.0 by adding 0.1 M NaOH, and the reaction was carried out at a constant temperature of 25° C. for 8 hours. After 8 hours, the pH of the solution was adjusted to neutral by adding 0.5 M HCl to terminate the reaction. The wood sample was washed with deionized water to obtain an oxidatively modified wood sample, which was freeze-dried and stored.
[0063] (3) Preparation of MOF / cellulose hybrid material: 0.223 g zirconium chloride and 0.166 g terephthalic acid were dissolved in 30 mL DMF respectively, and ultrasonically dispersed uniformly. The two solutions were mixed and ultrasonically dispersed for 10 min, and then placed in a stainless steel autoclave, and 1 g of the oxidatively modified wood sample obtained in step (2) was added, and reacted at 100° C. for 24 hours. After cooling, the wood sample was taken out and washed three times with DMF, and then freeze-dried to obtain the MOF / cellulose hybrid adsorption material.
[0064] In this example, under the optimal adsorption conditions in Example 1, the adsorption performance of the MOF / cellulose hybrid material was tested, and the maximum adsorption amount of crystal violet was measured to be 9.32 mmol / g.
[0065] Example 3
[0066] (1) Preparation of porous cellulose carrier: Take a 150 ml round-bottom flask, dissolve 1 g of sodium chlorite in 100 ml of deionized water, add acetic acid buffer to adjust pH = 4.6, ultrasonicate for 10 min, and add 1 g of dried balsa wood sample. Stir at constant temperature at 80 ° C for 18 hours to remove lignin. Finally, rinse the sample with deionized water to remove chemical residues, obtain a delignified wood sample, and store it in deionized water.
[0067] (2) Oxidative modification of cellulose carrier: The delignified wood sample (1 g) obtained in step (1) was immersed in 100 ml of an aqueous solution containing 0.1 g of TEMPO and 0.75 g of NaBr. Then, 10 ml of sodium hypochlorite solution was added dropwise to the solution to initiate an oxidation reaction. The pH value of the solution was maintained at 10.0 by adding 0.1 M NaOH, and the reaction was carried out at a constant temperature of 25° C. for 8 hours. After 8 hours, the pH of the solution was adjusted to neutral by adding 0.5 M HCl to terminate the reaction. The wood sample was washed with deionized water to obtain an oxidatively modified wood sample, which was freeze-dried and stored.
[0068] (3) Preparation of MOF / cellulose hybrid material: 0.223 g zirconium chloride and 0.166 g terephthalic acid were dissolved in 30 mL DMF respectively, and ultrasonically dispersed uniformly. The two solutions were mixed and ultrasonically dispersed for 10 min, and then placed in a stainless steel autoclave, and 1 g of the oxidatively modified wood sample obtained in step (2) was added, and the reaction was carried out at 150° C. for 24 hours. After cooling, the wood sample was taken out and washed three times with DMF, and then freeze-dried to obtain the MOF / cellulose hybrid adsorption material.
[0069] In this example, under the optimal adsorption conditions in Example 1, the adsorption performance of the MOF / cellulose hybrid material was tested, and the maximum adsorption amount of crystal violet was measured to be 12.64 mmol / g.
[0070] Example 4
[0071] (1) Preparation of porous cellulose carrier: Take a 150 ml round-bottom flask, dissolve 1 g of sodium chlorite in 100 ml of deionized water, add acetic acid buffer to adjust pH = 4.6, ultrasonicate for 10 min, and add 1 g of dried balsa wood sample. Stir at constant temperature at 80 ° C for 18 hours to remove lignin. Finally, rinse the sample with deionized water to remove chemical residues, obtain a delignified wood sample, and store it in deionized water.
[0072] (2) Oxidative modification of cellulose carrier: The delignified wood sample (1 g) obtained in step (1) was immersed in 100 ml of an aqueous solution containing 0.1 g of TEMPO and 0.75 g of NaBr. Then, 10 ml of sodium hypochlorite solution was added dropwise to the solution to initiate an oxidation reaction. The pH value of the solution was maintained at 10.0 by adding 0.1 M NaOH, and the reaction was carried out at a constant temperature of 25° C. for 8 hours. After 8 hours, the pH of the solution was adjusted to neutral by adding 0.5 M HCl to terminate the reaction. The wood sample was washed with deionized water to obtain an oxidatively modified wood sample, which was freeze-dried and stored.
[0073] (3) Preparation of MOF / cellulose hybrid material: 0.223 g zirconium chloride and 0.166 g terephthalic acid were dissolved in 30 mL DMF respectively, and ultrasonically dispersed uniformly. The two solutions were mixed and ultrasonically dispersed for 10 min, and then placed in a stainless steel autoclave, and 1 g of the oxidatively modified wood sample obtained in step (2) was added, and the reaction was carried out at 140° C. for 24 hours. After cooling, the wood sample was taken out and washed three times with DMF, and then freeze-dried to obtain the MOF / cellulose hybrid adsorption material.
[0074] In this example, under the optimal adsorption conditions in Example 1, the adsorption performance of the MOF / cellulose hybrid material was tested, and the maximum adsorption amount of crystal violet was measured to be 14.37 mmol / g.
[0075] Example 5: Adsorption of bisphenol A using MOF / cellulose hybrid adsorption material
[0076] The MOF / cellulose hybrid adsorption material obtained in Example 1 was subjected to an adsorption test on bisphenol A.
[0077] To investigate the effect of solution pH on adsorption performance, 10 mg of the MOF / cellulose hybrid adsorption material obtained in Example 1 was taken, and 60 mL of bisphenol A aqueous solution with an initial concentration of 0.1 mmol / L was taken. The pH of the solution was adjusted to 2 to 12, and the adsorption material was added to the solution and placed in a constant temperature oscillating water bath at 25°C. After 24 hours of oscillation adsorption, the adsorption amounts were compared by ultraviolet absorption spectroscopy test to obtain the optimal pH.
[0078] To explore the effect of adsorption time, take multiple portions of 10 mg MOF / cellulose hybrid adsorption material, take multiple portions of 60 mL of bisphenol A aqueous solution with an initial concentration of 0.1 mmol / L, adjust the solution pH to the best, add the adsorption material to the solution, and place it in a constant temperature oscillating water bath at 25°C, oscillate and adsorb for different times (1-24h), compare the adsorption amount through ultraviolet absorption spectrum test, and get the best adsorption time.
[0079] To investigate the effect of the initial dye concentration on the adsorption amount, take multiple portions of 10 mg MOF / cellulose hybrid adsorption material, measure 60 mL of bisphenol A aqueous solution with different initial concentrations, adjust the solution pH to the best, add the adsorption material to the solution, and place it in a constant temperature oscillating water bath at 25°C. The oscillation adsorption time is the best time. The adsorption amounts are compared through UV absorption spectroscopy testing to obtain the best initial concentration.
[0080] The adsorption performance test results show that when the adsorption temperature is 25°C, the optimal adsorption conditions are: the initial concentration of the solution is 1mmol / L, the pH is 6, and the adsorption time is 870min. Under these conditions, the maximum adsorption capacity of bisphenol A by the MOF / cellulose hybrid adsorption material is 0.98mmol / g.
[0081] Example 6: Adsorption of nonylphenol using MOF / cellulose hybrid adsorption material
[0082] The MOF / cellulose hybrid adsorption material obtained in Example 1 was used to perform an adsorption test on alkylphenol.
[0083] To investigate the effect of solution pH on adsorption performance, 10 mg of the MOF / cellulose hybrid adsorption material obtained in Example 1 was taken, and 60 mL of an aqueous solution of nonylphenol with an initial concentration of 0.1 mmol / L was taken. The pH of the solution was adjusted to 2 to 12, and the adsorption material was added to the solution and placed in a constant temperature oscillating water bath at 25°C. After 24 hours of oscillation adsorption, the adsorption amounts were compared by ultraviolet absorption spectroscopy test to obtain the optimal pH.
[0084] To explore the effect of adsorption time, take multiple portions of 10 mg MOF / cellulose hybrid adsorption material, take multiple portions of 60 mL of nonylphenol aqueous solution with an initial concentration of 0.1 mmol / L, adjust the solution pH to the best, add the adsorption material to the solution, and place it in a constant temperature oscillating water bath at 25°C, oscillate and adsorb for different times (1-24h), compare the adsorption amount through ultraviolet absorption spectroscopy test, and obtain the best adsorption time.
[0085] To investigate the effect of the initial dye concentration on the adsorption amount, take multiple portions of 10 mg MOF / cellulose hybrid adsorption material, measure 60 mL of nonylphenol aqueous solution with different initial concentrations, adjust the solution pH to the best, add the adsorption material to the solution, and place it in a constant temperature oscillating water bath at 25°C. The oscillation adsorption time is the best time. The adsorption amounts are compared through UV absorption spectroscopy test to obtain the best initial concentration.
[0086] The adsorption performance test results show that when the adsorption temperature is 25°C, the optimal adsorption conditions are: the initial concentration of the solution is 2mmol / L, the pH is 6, and the adsorption time is 960min. Under these conditions, the maximum adsorption capacity of nonylphenol by the MOF / cellulose hybrid adsorption material is 0.53mmol / g.
[0087] Example 7: Adsorption of Tetrabromobisphenol A Using MOF / Cellulose Hybrid Adsorption Material
[0088] The MOF / cellulose hybrid adsorption material obtained in Example 1 was subjected to an adsorption test on tetrabromobisphenol A.
[0089] To investigate the effect of solution pH on adsorption performance, 10 mg of the MOF / cellulose hybrid adsorption material obtained in Example 1 was taken, and 60 mL of an aqueous solution of tetrabromobisphenol A with an initial concentration of 0.1 mmol / L was taken. The pH of the solution was adjusted to 2 to 12, and the adsorption material was added to the solution and placed in a constant temperature oscillating water bath at 25°C. After 24 hours of oscillation adsorption, the adsorption amounts were compared by ultraviolet absorption spectroscopy test to obtain the optimal pH.
[0090] To explore the effect of adsorption time, take multiple portions of 10 mg MOF / cellulose hybrid adsorption material, take multiple portions of 60 mL of tetrabromobisphenol A aqueous solution with an initial concentration of 0.1 mmol / L, adjust the solution pH to the best, add the adsorption material to the solution, and place it in a constant temperature oscillating water bath at 25°C, oscillate and adsorb for different times (1-24h), compare the adsorption amount through ultraviolet absorption spectroscopy test, and obtain the best adsorption time.
[0091] To investigate the effect of the initial dye concentration on the adsorption amount, take multiple portions of 10 mg MOF / cellulose hybrid adsorption material, measure 60 mL of tetrabromobisphenol A aqueous solution with different initial concentrations, adjust the solution pH to the best, add the adsorption material to the solution, and place it in a constant temperature oscillating water bath at 25°C. The oscillation adsorption time is the best time. The adsorption amounts are compared through UV absorption spectroscopy test to obtain the best initial concentration.
[0092] The adsorption performance test results show that when the adsorption temperature is 25°C, the optimal adsorption conditions are: the initial concentration of the solution is 1mmol / L, the pH is 7, and the adsorption time is 1260min. Under these conditions, the maximum adsorption capacity of tetrabromobisphenol A by the MOF / cellulose hybrid adsorption material is 0.15mmol / g.
[0093] As can be seen from the above, Example 1 is a preferred embodiment of the present invention. The difference between Example 2 and Example 1 is that the preparation reaction temperature of the MOF / cellulose hybrid adsorbent material is lowered, resulting in a decrease in the removal rate of the adsorbent material for crystal violet. This is because the reaction temperature is not enough and the crystals of the synthesized zirconium-based metal organic framework adsorbent material cannot grow completely. The difference between Examples 3 and 4 and Example 1 is that the preparation reaction temperature of the MOF / cellulose hybrid adsorbent material is increased, resulting in a decrease in the removal rate of the adsorbent material for crystal violet. This is because the reaction temperature affects the structural pore size of the crystal, and too high a reaction temperature will destroy the structure of the crystal itself. When the crystallization temperature is 120°C, the synthesized zirconium-based metal organic framework adsorbent material has the highest removal rate for crystal violet, because the crystals of the synthesized zirconium-based metal organic framework adsorbent material just grow completely at this time. It can be seen from the test results of Examples 5, 6 and 7 that the hybrid adsorbent material of the present invention has a significant adsorption effect on trace organic pollutants in water.
Claims
1. Application of a MOF / cellulose hybrid adsorption material for adsorbing trace organic pollutants in water in the selective adsorption of crystal violet, characterized in that: The preparation method of MOF / cellulose hybrid adsorption material comprises the following steps: (1) dissolving sodium chlorite in water and adjusting the pH value to 2-6 with an acetic acid buffer to obtain a mixed solution; then adding wood to the mixed solution and subjecting it to hydrothermal treatment to obtain delignified wood; (2) immersing the delignified wood obtained in an aqueous solution containing TEMPO and NaBr, then adding sodium hypochlorite and adjusting the pH to 8-12 for oxidation reaction; after the reaction is completed, taking out the wood, washing it, and drying it to obtain oxidatively modified wood; (3) dissolving zirconium salt and terephthalic acid in N,N-dimethylformamide solvent respectively, and mixing to obtain two solutions; then mixing the two solutions, adding the oxidized modified wood obtained in step (2), and reacting at 100-150° C.; after the reaction, adjusting the pH to neutral, taking out the wood, washing, and drying to obtain a MOF / cellulose hybrid adsorption material; the zirconium salt is zirconium chloride; The mass ratio of zirconium chloride to terephthalic acid is (0.01-0.5):(0.01-0.3).
2. The use according to claim 1, characterized in that: In step (1), the concentration of sodium chlorite dissolved in water is (1-10) g / (10-100) mL.
3. The use according to claim 1, characterized in that: In step (1), the amount of the mixed liquid relative to the wood is (10-100) mL / g.
4. The use according to claim 1, characterized in that: In step (2), the amount of the aqueous solution containing TEMPO and NaBr relative to the delignified wood is (10-100) mL / g.
5. The use according to claim 1, characterized in that: In step (2), the mass ratio of TEMPO to NaBr in the aqueous solution containing TEMPO and NaBr is (0.001-0.1):(0.1-1).
6. The use according to claim 1, characterized in that: In step (3), the reaction temperature is 120°C.
Citation Information
Patent Citations
Metal organic framework / wood composite material, and preparation method and application thereof
CN112959446A
Preparation method of UIO-66 modified cotton fabric and adsorption of UIO-66 modified cotton fabric on reactive dyes
CN113663652A